Elastic surface waves in crystals. Part 1: Review of the physics - Favretto-Cristini, Nathalie; Komatitsch, Dimitri; Carcione, José M.; Cavallini, Fabio (Ultrasonics, 2011)
► Review of harmonic and transient elastic wave propagation in anisotropic media. ► Emphasis on surface-wave propagation in crystals, minerals and metals. ► Clarification of the terminology used for the surface waves. We present a review of wave propagation at the surface of anisotropic media (crystal symmetries). The physics for media of cubic and hexagonal symmetries has been extensively studied based on analytical and semi-analytical methods. However, some controversies regarding surfaces waves and the use of different notations for the same modes require a review of the research done and a clarification of the terminology. In a companion paper we obtain the full-wave solution for the wave propagation at the surface of media with arbitrary symmetry (including cubic and hexagonal symmetries) using two spectral numerical modeling algorithms.